Changing Forecasts - Forecasting Change: The US market for savings deposits in econometric models and the market for econometric models among depository institutions, 1960s to 1980s - Sebastian Knake (Humboldt University Berlin, 2023)
Since the late 1960s, the rising volatility of financial markets in the US has troubled econometricians and bank managers alike. Both professions have found it increasingly difficult to forecast savings deposit flows. This article explores these challenges by focusing on two developments. First, it explores the internal adjustment process among econometric models of the savings deposit market. To achieve this aim, I use the so-called FMP (MPS) macro model used by the Federal Reserve Board since 1970 and the deposit forecast model of the Philadelphia Saving Fund Society (PSFS), the oldest and largest savings bank in the US. I find that economists failed to find timeless determinants for the market for savings deposits, partly because the determinants of expectation formation of households kept changing. Instead, economists relied on a large number of time-dependent dummy variables. Second, the article shows how the conditions of the market for savings deposits shaped the demand for macroeconomic forecast models. Here, I again use PSFS as a case study. I show that the demand for econometric models in the banking industry skyrocketed in the 1970s but abated somewhat in the 1980s. While the rising volatility led bank managers to seek sophisticated tools to predict deposit flows, the deregulation of the banking industry and the accompanying change in customer behavior devalued macro models as a reliable forecast technique for individual banks. Instead, it became crucial for banks to predict the future behavior of competing institutions.
urn:nbn:de:kobv:11-110-18452/27203-7
Keywords: B23; N22; 330; Savings; Deposits; Interest Expectations; Portfolio Choice; Financial History; Econometric Modeling; Stagflation Period